226 Quantitative strength profiling in inclusion body myositis. Issue 12 (14th November 2019) - Lilleker, James B; Oldroyd, Alexander; Chinoy, Hector; Miller, James AL
Abstract : Background: Inclusion body myositis (IBM) is a rare idiopathic inflammatory myopathy subtype. Our study aimed to describe the disease progression rate in IBM using measures of muscle strength and functional assessment tools. Methods: Retrospective analysis of quantitative muscle strength data and functional assessment tool results (IBM Functional Rating Scale [IBM-FRS] and the Neuromuscular Symptom and Disability Score [NSS]), systematically collected from verified IBM cases (July 2003 to March 2015) at a UK neuromuscular clinic. Yearly rate of strength change was estimated for each muscle group and associations between with the IBM-FRS/NSS were examined using simple linear regression. Results: Data from 80 IBM cases (44% female) were analysed, a total of 232 person-years and a median 2.3 years (IQR 0.6, 4.4) follow-up. Similar rates of deterioration were found for right and left sided muscle groups. Annual rate of strength loss was greatest for grip, pinch and knee extension (-5.5% [95% CI -6.3, -4.6], -16.0% [-18.4, -13.5] and -7.1% [-7.6, -6.5]). The rate of strength loss was greatest for males. Increased strength measurements were associated with improved IBM-FRS/NSS scores for most muscle groups. Conclusion: This is the first long-term study to comprehensively demonstrate quantitative strength change in a large IBM cohort. We provide valuable natural history data to support discussions regarding prognosis, focus effective choice of outcome measures and inform required study numbers for future clinical trials.